2022
DOI: 10.3389/fcvm.2022.866901
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Carboxyl-Terminal Hydrolase L1 of Cardiomyocytes Promotes Macroautophagy and Proteostasis and Protects Against Post-myocardial Infarction Cardiac Remodeling and Heart Failure

Abstract: Ubiquitin carboxyl-terminal hydrolase L1 (UCHL1) is a deubiquitinase known to play essential roles in the nervous tissue. Myocardial upregulation of UCHL1 was observed in human dilated cardiomyopathy and several animal models of heart disease, but the (patho)physiological significance of UCHL1 in cardiomyocytes remains undefined. Hence, we conducted this study to fill this critical gap. We produced cardiomyocyte-restricted Uchl1 knockout (CKO) by coupling the Uchl1-floxed allele with transgenic Myh6-Cre in C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Azad et al 13 demonstrated that prolonged hypoxia can induce autophagic cell death, which may represent a potential target for preventing cell death. Wu et al 14 reported that autophagy induction following cardiac hypoxia or ischemic injury may play a pathogenic role in heart disease. In view of the controversy of autophagy, the fact is that apoptosis and autophagy interact and play a key role in regulating cell survival during HF.…”
Section: Introductionmentioning
confidence: 99%
“…Azad et al 13 demonstrated that prolonged hypoxia can induce autophagic cell death, which may represent a potential target for preventing cell death. Wu et al 14 reported that autophagy induction following cardiac hypoxia or ischemic injury may play a pathogenic role in heart disease. In view of the controversy of autophagy, the fact is that apoptosis and autophagy interact and play a key role in regulating cell survival during HF.…”
Section: Introductionmentioning
confidence: 99%
“… Geng et al (2022) compared the ischemic heart injury group with the control group and found the overexpression of UCHL1 has a protective effect on myocardial injury after myocardial infarction. Upregulation of UCHL1 can prevent cardiac remodeling and dysfunction after myocardial infarction by supporting autophagy flow and protein homeostasis ( Wu et al, 2022 ). For the GPC6 gene, a previous study found that compared to patients with heart failure after myocardial infarction, patients without heart failure had significantly lower glypican-6, suggesting that GPC6 may be a protective gene for heart failure after myocardial infarction ( Ozturk et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…No abnormalities were observed in the cardiac development of UCHL1-specific knockout mice before 14 weeks of age (Ref. 99 ) ( Fig. 2 ).…”
Section: Role Of Deubiquitinases In Cardiac Diseasementioning
confidence: 93%